Pendampingan Pelaporan SPT Pajak Bagi Wajib Pajak Pribadi Di Kantor Kecamatan Tuah Madani Pekanbaru - Anggriani , Irien Violinda; Muat, Susnaningsih; Triandani, Sahwitri; Arisandy, Nelsi (LPPM UMRI, 2023)
Tax is an obligation that must be fulfilled by every citizen. Current tax revenue is not in line with the government's expectations, because taxpayers do not pay their tax obligations on time and even some entrepreneurs do not report their transactions, so tax revenue is not optimal. Therefore understanding of the importance of paying taxes is needed for the sake of all the Indonesian citizen. We, as a community service team, work closely with the Regional Office of the Directorate General of Taxes of Riau Province through the Tax Center of the Faculty of Economics and Social Sciences, State Islamic University of Sultan Syarif Kasim Riau, as a companion for Tax Volunteers in providing assistance in filling out Annual Tax Returns for personal Taxpayers in reporting the wealth electronically. The method used is Participatory Action Research which is the implementation of dedication to define a problem or apply information into action as a solution to the problem or activity being carried out. The purpose of this community service is to provide convenience and satisfaction for personal taxpayers and tax volunteers who have successfully reported their wealth and also succeeded in assisting taxpayers.